Enhancing biodiversity through market-based strategy: Organic agriculture - Marie Mondeil; Sununtar Setboonsarng (Asian Development Bank Institute (ADBI), 2009)
The diversity of plant genetic resources (PGR) from which the world's food crops are derived is steadily declining, due in part to the reliance of modern agriculture on a limited number of improved varieties. This erosion of genetic variation can lead to increased vulnerability to plant pests and diseases as well as to the potential loss of future varieties that will be required to meet the challenges brought about by climate change. Having recognized that the protection and sustainable management of PGR is critical to ensuring food security and alleviating poverty, governments and the international community have used public funds to establish seed banks and protected areas in an effort to preserve the existing PGR. However, given their small scope and susceptibility to genetic drift, the effectiveness of these public efforts may be limited. The vast majority of remaining PGR diversity is in the hands of smallholder farmers in remote areas of developing countries who cultivate a wide array of traditional varieties. This paper argues that a comprehensive system of market-based incentives is necessary to ensure that smallholder farmers continue to conserve plant genetic resources. Promoting certified organic agriculture has emerged as one of the most promising market-based development strategies for protecting PGR diversity. By providing incentives in the form of premium prices as a form of payment for environmental services, farmers are encouraged to adopt sustainable cultivation of local varieties and thus maintain high levels of biodiversity, without a burden on public expenditures.
Keywords: Q57; Q27; Q56; 330